Early Childhood Science Education: Research Trends in Learning and Teaching - Ravanis, Konstantinos (2022)
This volume consists of a collection of articles that touch on very different research aspects within a broad scientific field known in recent years as Early Childhood Science Education. The field has gradually emerged from the interaction between three distinct scientific areas of theory and research: Early Childhood Education, Psychology, which is oriented towards the study of learning, and Science Education. At the center of the progress in this field are efforts to initiate children aged 4-8 years in the Physical and Biological Sciences. A wide range of research themes have developed around this main axis: children's mental representations of phenomena of the natural world and scientific concepts, the study of the implementation and effectiveness of specific teaching activities related to curricula or activities focusing on the specific characteristics of teaching processes such as reasoning, explanation, communication, interaction or argumentation, the issue of teachers' relevance to the teaching of science, the use of pecialized teaching materials, the emergence of the issue of scientific skills, the highly contemporary issue of the differentiation and inclusion of children in the world of science, important socio-scientific issues, the role of family-related factors etc. Within this context, this collective book aims to reflect contemporary research trends in the field of Early Childhood Science Education.